Home-based treatment and nursing plan of a patient diagnosed with mild-to-common coronavirus disease 2019 - Bing-Rui Wei; Dian Francis Savellano; Cui-Huan Hu (Wolters Kluwer Medknow Publications, 2020)
To date, there are no known specific antiviral medicines recommended for coronavirus disease 2019 (COVID-19). The treatment mainly focuses on the improvement of the immunity of the individual and the application of palliative treatment. A case of a patient diagnosed with mild COVID-19 and then later developed common COVID-19 which was treated and closely monitored at home will be presented. The patient was advised for self-quarantine with several prescribed medications. Nursing home and self-care advice were given to the patient, including a change of lifestyle for the duration of the isolation, medication advice, symptomatic care, change of diet, how to monitor the progress of the disease, psychological care, and follow-up instructions. During the course of the nursing plan, the patient showed significant improvements, and normal life functions were restored. On February 05, 2020, novel coronavirus nucleic acid test showed negative after re-examination; the patient was cured. Therefore, providing adequate nursing plan for home-based self-care treatment can effectively cure mild and common cases of COVID-19.